When Support Is Not Enough: Academic Supervision Style, Academic Support, and Student Stress in Thesis Supervision - Amila Shaliha; Rahima Nurviani; Muhammad Anggung Manumanoso Prasetyo (Educazione: Journal of Education and Learning, 2026)
Academic stress among final-year students during thesis writing remains a persistent concern in higher education, yet the mechanism linking the supervisory relationship to student stress is still poorly understood. While supervision style and academic support are each assumed to influence stress, few studies have tested academic support as a mediating variable in this relationship. This study aims to analyze the effect of academic supervision style on academic stress and to examine the mediating role of academic support among final-year students. A quantitative survey design was employed, involving 150 final-year students of the Faculty of Tarbiyah and Teacher Training selected through simple random sampling. Data were collected using a Likert-scale questionnaire and analyzed through Structural Equation Modeling based on Partial Least Squares (SEM-PLS) using SmartPLS, with bootstrapping to test direct and indirect effects. The results reveal that academic supervision style significantly influences academic support, whereas neither supervision style nor academic support significantly affects academic stress, either directly or through mediation, indicating that student stress is driven primarily by determinants beyond the supervisory relationship. These findings carry important implications: institutions should reposition academic support as a foundation for student autonomy and resilience within a transformative model of supervision, while addressing student stress through complementary interventions that target structural and intrapersonal pressures directly rather than relying on improved supervision alone.